Vocabulary Learning Strategies by JFL Good Learners in the Digital Era - Eka Marthanty Indah Lestari; Dewi Puspitasari (IZUMI, 2021)
Vocabulary is an integral aspect when learning a foreign language. The issue discussed in this research includes learning new vocabularies by Japanese language learners who are competent and the relevance of vocabulary-learning strategy by Oxford (1990) to foreign language learners' current condition. This research aims to elaborate on the relevant vocabulary-learning strategy for foreign learners of the Japanese language. The research methodology is qualitative, with semi-structured interviews by adopting the questionnaire by Saengpakdeejit (2014). The vocabulary-learning strategy is classified based on the taxonomy of vocabulary learning strategy by Oxford (1990), Schmitt (1997), and Churches (2009). The result shows that Japanese language learners who are competent apply the vocabulary learning strategy, as Oxford (1990) stated. The dominant strategy used by the participants is a cognitive strategy, which allows new vocabularies to be stored in the participant's memory. Furthermore, information related to new vocabularies needs to be stored in the participant's memory using vocabularies. Besides, a competent Japanese language learner can use the learning resources, printed materials, and digital application to improve the vocabularies.